Effects of High-Pretension Support System on Soft Rock Large Deformation of Perpendicularly Crossing Tunnels - Li Gan; Ma Weibin; Tian Siming; Zhou Wenhao (Advances in Civil Engineering)
The control mechanism of prestressed support system is studied by means of three-dimensional discrete element numerical simulation, theoretical analysis, and field measurement. The actual project is selected to analyze, and the control effect is demonstrated. The theoretical analysis results show that the prestressed support can improve the self-bearing capacity of surrounding rock, which is conducive to the stability of the surrounding rock. The numerical calculation shows that, under the control of the long and short cables, the prestress can spread effectively and form two bearing arches. The deformation is difficult to control, which is in the arch crown and the arch shoulder of the tunnel intersection. However, the deformation of the surrounding rock decreases with the increase of prestress. Through the analysis of the measured results, it shows that the pretension support design scheme can effectively control the large deformation of the surrounding rock.